Feeding damage evaluation of the mirid bug, Helopeltis bakeri Poppius on cacao pods - Pag-ong, Anthony Ian G.; Barrion, Alberto T.; Amalin, Divina M. (2024)
Actual observations and documentation of cacao pests feeding on the pods in the field are very few. The cacao mirid bug, Helopeltis bakeri Poppius, was laboratory-reared and released [21 pairs = Tree 1; 17 pairs = Tree 2; 21 pairs = Tree 3] in three randomly chosen cacao trees under controlled settings from October 2019–March 2020 with the aim of observing and documenting cacao pests feeding on the pods in the field to have insights into the proper pest action threshold. A coefficient score of 4.93 on a 0–5 rating scale described “heavy damage” as > 50% of feeding lesion marks on 28 out of 30 pods (93%) were visible. The first feeding lesions were observed in an average of 37 days but came as early as 10 d upon release of H. bakeri. Within this time of observing the initial feeding lesions, there would only be 39 d before the whole pod is scorched due to black pod disease. The study shows the harmfulness of this cacao pest and highlights the need for integrated pest management to reduce the reliance on chemical control, which has been the default strategy for too long.
Keywords: Cacao diseases and pests